COVID-19 vaccine hesitancy among parents in Low- and Middle-Income Countries: A meta-analysis - Abu El Kheir-Mataria, Wafa; Saleh, Basma M.; El-Fawal, Hassan; Chun, Sungsoo (Frontiers in Public Health, 2023)
Background: vaccination is the most effective method to prevent the spread of infectious diseases. Nevertheless, vaccine hesitancy has been an issue. Parental hesitancy towards vaccines is a major part of the problem. Covid-19 vaccine acceptance is no different, it poses another challenge in facing the pandemic. In Low- and Middle-Income Countries (L&MICs) several studies measured parents’ acceptance to vaccinate their children against Covid-19 and resulted in different acceptance proportions. Aims: the paper aims at obtaining a precise estimate of the overall proportion of L&MICs’ parents accepting to vaccinate their children against Covid-19 and identifying the main determinant of their decisions. Methods: This meta-analysis follows the PRISMA 2020 statement on updated guidelines and the checklist for reporting systematic reviews. Studies published between December till February 2022 were assessed for inclusion. The final effect size (i.e., the proportion of parents in L&MICs accepting to vaccinate their children against Covid-19) was measured using the Arcsine proportions method. Analysis was done using R program. Results: The proportion of parents in L&MICs accepting to vaccinate their children against Covid-19 is 49%. The major reason for their acceptance is their belief that Covid-19 vaccine is fundamental to the fight against the pandemic while the most common factor for parents’ hesitancy to vaccinate their children against Covid-19 is their concerns about vaccine efficacy, safety, and possible side effects. Conclusion: the proportion of parents in L&MICs accepting to vaccinate their children against Covid-19 is lower than the global level. To increase parental acceptance, responsible authorities should concentrate on increasing their population’s trust in the government and in vaccine manufacturers. As well as concentrating on increasing acceptance of the vaccine idea in general.